Analysis of reliability and accuracy of lunar core detection based on Apollo moonquake observation - Yang, Biao; Wang, Yanbin (Frontiers in Astronomy and Space Sciences, 2023)
Introduction: In the 1960s, the Apollo missions deployed seismometers on the near side of the Moon, and the obtained moonquake data enabled the seismic study of internal structure of the Moon. The lunar seismic waveforms are dominated by strong coda waves caused by scattering in the near surface, which masks the reflected and converted waves from the discontinuities inside the Moon. The Double Array Stacking method is an important technique to enhance the reflected and converted waves. However, its performance would be affected by many factors including signal to noise ratio, arrival time errors, differences in amplitude and polarity of waveforms caused by different station azimuth, and source mechanisms, thus needs to be further analyzed. Method: In this study, we use the pseudo-spectral and finite-difference hybrid method on staggered grid to simulate wave propagation of deep moonquakes, considering near surface scattering, to analyze the influence of the above factors on the stacking results of reflected and converted phases from outer core of the Moon. Results and discussion: Our results indicate that coda and noises would greatly reduce the stacking energy but have no significant impact on the peak position of the stacked waveforms. The arrival time errors have a significant influence on the vertical component of ScP phase and the radial component of the ScS phase, but have little influence on the transverse component of ScS phase. The difference in amplitude also leads to differences in stacking energy, but the stacking image shows good consistency in the shape. When the polarities of seismic phases are relatively consistent, the peak of the stacking energy comes from reflected phases from the core mantle boundary of the Moon. This research may be helpful to improve the detection accuracy of the internal structure of the Moon and provide a solid reference for the deployment of future seismic stations, which is of great significance for understanding the formation and evolution process of the Moon.